2012
DOI: 10.1007/s13312-012-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prospects for prevention of rotavirus disease in India

Abstract: The epidemiology and burden of rotavirus diarrhea is fairly well characterized in India. Introducing rotavirus vaccine into the UIP, along with adequate surveillance, should be an important part of efforts to reduce diarrhea mortality, the third leading cause of death among Indian children, and achieve the country's MDG goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 57 publications
7
54
0
1
Order By: Relevance
“…5e7 Advances in hygiene and sanitation have reduced the predominance of the other gut pathogens, while leaving rotavirus incidence almost unaffected. 8 Rotavirus vaccines are being projected as a solution to this problem. Availability of efficacious rotavirus vaccines has warranted extensive epidemiological studies on rotavirus diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…5e7 Advances in hygiene and sanitation have reduced the predominance of the other gut pathogens, while leaving rotavirus incidence almost unaffected. 8 Rotavirus vaccines are being projected as a solution to this problem. Availability of efficacious rotavirus vaccines has warranted extensive epidemiological studies on rotavirus diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…In previously published studies also, G1P [8] was the most prevalent genotype identified in other parts of India including South India. [15][16][18][19][20] G1P [4], G1P [6] and G2P [4] were identified in 7.34%, 4.59% and 6.42% specimens, respectively. In previous studies from India, G2P [4] was found to be one of the predominant strains.…”
Section: Discussionmentioning
confidence: 99%
“…In India, diversity of rotavirus strains varies geographically, with G1 and G2 as the predominant strains. [17][18][19][20] G9P [4] and G9P [8] were detected in 3.70% and 1.83% of the specimens, respectively. G12P [6] and G12P [8] were detected in 3.70% and 0.91% of the specimens tested, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding seasonality, some studies in India have found no association between rotavirus infection and the time of year 13,21 .Other studies have observed an increase in rotavirus-associated diarrhea during the winter months, October-February, throughout the country 12,22,23 .…”
Section: Severity Of Rotavirus Diarrhoea Was Shown Inmentioning
confidence: 99%